2008
DOI: 10.1161/circulationaha.107.732990
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G-Protein Signaling Subtype 4 Mediates Antihypertrophic Effect of Locally Secreted Natriuretic Peptides in the Heart

Abstract: Background-Mice lacking guanylyl cyclase-A (GC-A), a natriuretic peptide receptor, have pressure-independent cardiac hypertrophy. However, the mechanism underlying GC-A-mediated inhibition of cardiac hypertrophy remains to be elucidated. In the present report, we examined the role of regulator of G-protein signaling subtype 4 (RGS4), a GTPase activating protein for G q and G i , in the antihypertrophic effects of GC-A. Methods and Results-In cultured cardiac myocytes, treatment of atrial natriuretic peptide st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 46 publications
3
79
0
Order By: Relevance
“…Knockdown of RGS2 and RGS4 Does Not Affect the Effect of PDE5-IIt has been recently reported that PKG-dependent phosphorylation of RGS2 and RGS4 mediates the anti-hypertrophic effects in mouse hearts (32,40,41). Thus, we next examined the involvement of RGS proteins in the inhibition of agonistinduced Ca 2ϩ responses by PDE5 inhibition, using siRNAs for RGS2 and RGS4.…”
Section: Suppression Of Mechanical Stretch-induced Ca 2ϩmentioning
confidence: 96%
“…Knockdown of RGS2 and RGS4 Does Not Affect the Effect of PDE5-IIt has been recently reported that PKG-dependent phosphorylation of RGS2 and RGS4 mediates the anti-hypertrophic effects in mouse hearts (32,40,41). Thus, we next examined the involvement of RGS proteins in the inhibition of agonistinduced Ca 2ϩ responses by PDE5 inhibition, using siRNAs for RGS2 and RGS4.…”
Section: Suppression Of Mechanical Stretch-induced Ca 2ϩmentioning
confidence: 96%
“…We next tested whether membrane-localized PKG1α-targeted proteins were preferentially impacted by PKG1α C42S , focusing on 3 known candidates. Regulator of G protein signaling (RGS) RGS2 and RGS4 bind to and are activated by PKG1α, blunting the hypertrophy and dilation otherwise induced by Gαq activation and mechanical stress (14,15). To test whether reduced PKG1α favored RGS2/4 activation, one or both RGS genes were suppressed by siRNA (Supplemental Figure 12A).…”
Section: Signaling In Pkg1αmentioning
confidence: 99%
“…We reported that PKG activation by PDE5 inhibitor fails to de-activate multiple hypertrophy signaling cascades in hearts lacking RGS2, resulting in a lack of the antihypertrophic/remodeling effect, 55 and Tokudome et al reported that RGS4 overexpression ameliorates cardiac spontaneous hypertrophy in NPRA (GCA) null animals. 56 Recent study suggested that PKG-RGS2 is also involved in the ANP-GCA antihypertrophy. 57 Lastly, it is worthwhile mentioning the differential response between the right and left heart to PDE5 inhibitor in hypertrophy/remodeling.…”
Section: Cgmp Regulation Of Cardiac Hypertrophy and Remodelingmentioning
confidence: 99%